Comparison of Efficacy of Positron Emission Tomography/Computed Tomography with Contrast-Enhanced Computed Tomography in Pretreatment Evaluation of Head and Neck Cancers: An Institutional Experience - Jain, Mayuri; Sarin, Arti; Suhag, V; Gahlot, GPS; Jain, Anurag; Bandhopadhya, A (Indian Journal of Medical and Paediatric Oncology, 2019)
Introduction: Head and neck squamous cell carcinomas (SCCs) constitute 5.4% of all cancers worldwide, and 23% of all cancers in males and 6% of all cancers in females diagnosed in India. Lots of ambiguity exists in primary, nodal, and metastatic workup of these patients, especially in developing countries. Aim: The study was designed to compare the accuracy of whole-body positron emission tomography/computed tomography (WBPET/CT) scan with contrast-enhanced CT (CECT) face and neck as pretreatment evaluation for staging workup and management decision and to confirm the nodal findings on imaging with fine-needle aspiration cytology (FNAC). Design: It was a single-institute, prospective, observational, interventional study over a 2-year period. All cases of SCC of upper aerodigestive tract who were scheduled for definitive treatment concurrent chemoradiotherapy or radiotherapy were evaluated with routine investigations followed by imaging in the form of CECT face and neck and 18F-fluorodeoxyglucose (FDG) WBPET/CT. Results: In the 40 enrolled patients, all underwent CECT face and neck and WBPET/CT. During initial workup, biopsy was taken from primary site and FNAC was done from neck nodes for diagnosis and for staging. In 40 patients, CECT neck showed nodal metastasis in 39 patients; however, FNAC came positive in 38 cases. PET/CT showed nodal metastasis in 38 patients; however, FNAC came positive in 38 cases. Any node with Standardized uptake value (SUV) >2.5 was taken as suspicious lesion and FNAC was done. Sensitivity of CECT and PET/CT was 97.36% and 100%, respectively, while the specificity was 0% and 100%, respectively. Positive predictive value calculated for CECT and WBPET was 94.87% and 100%, respectively, while the negative predictive value for CECT and WBPET was 0% and 100%, respectively. Conclusion: In head and neck SCC, FDG-PET/CT is more accurate than CECT in staging of the neck.
Keywords: Computed tomography scan; fine-needle aspiration cytology; Head and Neck Cancers; positron emission tomography scan